Stem Cells Service Legality Post-Application of Law Number 36 Year 2009 about Health - Dian Andriani Ratna Dewi; Nasser Nasser; Tiarsen Buaton; Topane Gayus Lumbuun (Green Publisher Indonesia, 2022)
The development of stem cells services has grown rapidly throughout the world since 2004, as well as in Indonesia. This is because stem cells have unique properties that can differentiate into various cells types, making it promising to repair tissue damaged by various diseases, especially degenerative conditions. The purpose of this study was to obtain an overview of the regulation of stem cells services so that it can be carried out to the public after the enactment of the Health Law Number 36 of 2009 and to obtain an overview of the implementation of the law in stem cells regulation that is not yet comprehensive. The research methodology used is juridical normative, with a statutory approach, a conceptual approach. Also by using a comparative approach with other countries. This study analyzes substantially the regulation of stem cells and/or cells services based on Minister of Health Regulation number 32 of 2018 concerning stem cells and/or cells services and the implementation of laws against violations in their implementation. The regulations that are not yet comprehensive have in the competence of doctors who carry out stem cells services both as standardized therapy and service-based research that has not been certified, as well as the implementation of the law to use laws and regulations that are generally used for cases of non-specific illegal acts that result in prosecution. which is multi-layered. So that it is necessary to regulate stem cells according to the hierarchy of legislation and need to revise Minister of Health Regulation number 32 of 2018 so that it can be implemented safely and effectively and accommodate the orientation of technology development in the stem cells sector in Indonesia.